STRATEGI PROMOSI DESTINASI WISATA YOGYAKARTA DALAM AKUN INSTRAGRAM @thepotraitjogja - Yogyanti, Devita Widyaningtyas; Atiqah, Annisaa Nurul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
This research is a study that took @thepotraitjogja instagram account as the research object. This research focuses on how instagram @thepotraitjogja accounts promote the city of Yogyakarta to tourism. The method used in this research is descriptive qualitative method. The results of the study it is known that instagram accounts @theportraitjogja image use a variety of language styles in their caption to influence readers' feelings. The feeling that you want to cause is a feeling of love and missing to Yogyakarta. Therefore, through the style of the language used, the instagram seeks to bring the image of a lover who is warm, charming and longed for in the city of Yogyakarta. The emotional closeness that is expected to be difficult after reaching the image is expected to strengthen the readers' desire to come to visit the city of Yogyakarta, just like coming to visit a lover. There are three styles of language used to bring up the image, among others: (1) comparative language style consisting of litotes, personification, metaphor, hypocorism, hyperbole, allegari and simile language styles, (2) affirmation language style consisting of language style repitition, parallelism and silepsis; and (3) the opposing language style consisting of the pardox language style. Keywords : promotion strategy, language style, tourism destination